Brain Plasticity Can Predict the Cochlear Implant Outcome in Adult-Onset Deafness - Han, Ji-Hye; Lee, Hyo-Jeong; Kang, Hyejin; Oh, Seung-Ha; Lee, Dong Soo (Frontiers in Human Neuroscience, 2019)
Sensory plasticity, which is associated with deafness, has not been as thoroughly investigated in the adult brain as it has in the developing brain. In this study, we examined the brain reorganization induced by auditory deprivation in people with adult-onset deafness and its clinical relevance by measuring glucose metabolism before cochlear implant (CI) surgery. F-18 fluorodeoxyglucose positron emission tomography (18F-FDG-PET) scans were performed in 37 postlingually deafened patients during the preoperative workup period, and in 39 normal-hearing (NH) controls. Behavioral CI outcomes were measured at one year after implantation using a phoneme identification test with auditory cueing only. In the deaf individuals, areas involved in the auditory pathway such as the inferior colliculus and bilateral superior temporal gyri were hypometabolic compared to the NH controls. The hypometabolism observed in the deaf auditory cortices gradually returned to levels similar to the controls as the duration of deafness increased. However, contrary to our previous findings in congenitally deaf children, this metabolic recovery failed to have a significant prognostic value for the recovery of the speech perception ability in adult CI patients. In a broad occipital area centered on the primary visual cortices, glucose metabolism was higher in the deaf patients than the controls, suggesting that the area had become visually hyperactive for sensory compensation immediately after the onset of deafness. In addition, a negative correlation between the metabolic activity and behavioral speech perception outcomes was observed in the visual association areas. In the medial frontal cortices, cortical metabolism in most patients decreased, but patients who had preserved metabolic activities showed better speech performance. These results suggest that the auditory cortex in people with adult-onset deafness is relatively resistant to cross-modal plasticity, and instead, individual traits in late-stage visual processing and cognitive control seem to be more reliable prognostic markers for adult-onset deafness.